Inhibition of NF-kB Signaling by Extract of Male Papaya Flowers (Carica papaya L.) in Chronic Inflammatory Disease Models - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo (Biology, Medicine, & Natural Product Chemistry, 2026)
Chronic inflammation is closely associated with persistent activation of Nuclear Factor-kappa B (NF-kB) signaling pathways, which regulate the expression of pro-inflammatory cytokines and inflammatory mediators involved in various chronic inflammatory diseases. The present study investigated the anti-inflammatory activity of male papaya flower (C. papaya L.) extract through inhibition of NF-?B signaling in lipopolysaccharide (LPS)-induced RAW 264.7 macrophages. Male papaya flowers were extracted using 70% ethanol and subjected to phytochemical screening, total phenolic content (TPC), and total flavonoid content (TFC) analyses. Cytotoxicity was evaluated using the MTT assay, while anti-inflammatory activity was assessed through nitric oxide (NO) production, enzyme-linked immunosorbent assay (ELISA) for pro-inflammatory cytokines, western blot analysis, immunofluorescence staining, and DPPH radical scavenging assay. Phytochemical analysis revealed the presence of flavonoids, phenolics, alkaloids, tannins, saponins, and terpenoids. The extract demonstrated high TPC and TFC values of 186.42 ± 5.31 mg GAE/g extract and 97.25 ± 3.84 mg QE/g extract, respectively. Male papaya flower extract exhibited low cytotoxicity at concentrations below 200 µg/mL and significantly suppressed nitric oxide production, TNF-alpha, IL-1beta, and IL-6 secretion in LPS-induced macrophages (p < 0.05). Western blot analysis showed that the extract inhibited phosphorylation of NF-kB p65 and I?B? proteins while reducing COX-2 and iNOS expression. Immunofluorescence analysis further confirmed inhibition of NF-kB nuclear translocation. In addition, the extract demonstrated strong antioxidant activity with an IC50 value of 58.4 µg/mL in the DPPH assay. These findings suggest that male papaya flower extract possesses potent anti-inflammatory and antioxidant properties through suppression of NF-kB signaling pathways and may serve as a promising natural therapeutic candidate for chronic inflammatory diseases.